Bacterial Vaginosis: A Systematic Analysis on Current Treatments for Pregnant Women - M, Manipon; M, Dale Christian; B, Bugarin; S, Kimberly Claire; M, Mahinay; Millare, Jian S.; C, Krisha Joyce; P, Papa; F, Margareth Louise; N, Nuñez; B, Lara Patricia; M, Mabbagu; et al. (Asian Journal of Biological and Life Sciences)
Bacterial vaginosis (BV) is a vaginal infection that causes discharge, odor, and irritation, characterized by a shift in the vaginal flora from the dominant Lactobacillus to a polymicrobial flora. It is a commonly reported microbiological syndrome among women of childbearing age. It has been associated with a wide array of health issues, including preterm births, pelvic inflammatory disease, increased susceptibility to HIV infection, and other chronic health problems. This systematic review provides: (1) an overview of bacterial vaginosis (BV), (2) an evaluation of the effectiveness of current treatments for BV for pregnant women, and (3) summarizes the treatment recommendations for pregnant women with bacterial vaginosis (BV). This review makes use of articles and studies found in databases such as Pubmed, Web of Science, and Cochrane. Systematic review and randomized trials have shown that treating bacterial vaginosis in pregnancies with metronidazole and clindamycin do have a significant effect in reducing the risk of preterm birth (PTB). Additionally, probiotics appear to have a significant effect in reducing the risk of preterm birth (PTB), but the evidence is still inconclusive, and further research is needed.
Keywords: Bacterial Vaginosis; Pregnant Women; Preterm Labor; Sexually Transmitted Diseases; Treatment